Influence of Constipation in the Behavior of Circulating Alpha- and Beta-CGRP Levels in Chronic/High-Frequency Migraine Patients After CGRP Monoclonal Antibodies - Gabriel Gárate; Marcos Polanco; Jorge Madera; María Muñoz-San Martín; Marta Pascual-Mato; Vicente González-Quintanilla; Julio Pascual (Biomedicines)
Background/Objectives: Migraines contain neurological and gastrointestinal manifestations. The first specific migraine preventive drugs, CGRP monoclonal antibodies (mAbs), though efficacious and very well-tolerated in general, induce constipation as their main adverse event. Our goal was to analyze the role of the two isoforms of CGRP in the development of constipation in patients treated with mABs. Methods: We prospectively measured by ELISA circulating alpha- and beta-CGRP levels in 133 high-frequency episodic/chronic migraine patients before and three months after mAbs treatment and correlated these levels with a number of clinical variables, including the development of constipation during this treatment. Results: Twelve patients (9.0%) noticed de novo constipation with mAbs. Demographics, efficacy end-points, profile of preventive treatment, and comorbidities, with the exception of anxiety/depression, were superimposable between patients with or without emergent constipation. Basal alpha-CGRP levels (49.5 [29.2–73.8] pg/mL) significantly decreased at month three of treatment (40.5 [20.4–61.0] pg/mL; p < 0.0001), both in patients with and without emergent constipation. Pre-treatment circulating beta-CGRP levels (4.0 [2.1–6.2] pg/mL) remained unchanged after three months of treatment (4.3 [2.5–6.0] pg/mL; p = 0.574) in the whole series but were selectively reduced in patients with emergent constipation (p = 0.034). Conclusions: This is the first work exploring the role of the two isoforms of CGRP in the pathophysiology of constipation with mAbs. Our results suggest that the antagonism on the alpha-CGRP isoform plays a relevant role in the antimigraine action of mABs but not in the development of constipation. By contrast, the specific reduction in beta-CGRP levels in patients with emergent constipation supports the role of beta-CGRP antagonism in the development of this adverse event.